Inhibitory effects of nipa palm vinegar on the carbohydrate hydrolysing enzymes - Farjana Yasmin,; Swaminathan Meyyammai,; Khairul Niza Abd Razak,; Nozlena Abdul Samad,; Widyawati, Tri; Nor Adlin Yusoff, (Universiti Kebangsaan Malaysia, 2023)
Nipa palm vinegar has been traditionally used to manage blood glucose levels by diabetic patients in Southeast Asia. This study was designed to evaluate the efficacy of nipa palm vinegar in inhibiting the activity of carbohydrate hydrolyzing enzymes, α-glucosidase, and α-amylase. In vitro spectrophotometric assays were used to evaluate the inhibitory activity of nipa palm activity against α-glucosidase and α-amylase. To confirm the in vitro findings, an oral starch tolerance test in the normoglycemic Sprague Dawley rat was conducted. Acarbose was used as the positive control for both tests. Nipa palm vinegar at a concentration ranging from 4000 to 62.5 mg/mL inhibited the activity of α-glucosidase and α-amylase in a concentration-dependent manner with the respective IC50 values of 144.50 ± 1.1 mg/mL and 90.30 ± 1.7 mg/mL. It also exerted uncompetitive inhibition against α-glucosidase and competitive inhibition towards α-amylase. In vivo oral starch tolerance test showed a significant (p < 0.05) postprandial glucoselowering effect of nipa palm vinegar at the doses of 2 mL/kg and 1 mL/kg body weight as compared to the control. In a conclusion, this study demonstrated that nipa palm vinegar suppressed the rise in postprandial glucose levels partly by inhibiting the activity of digestive enzymes.